Perancangan Mobil Remot Kontrol Arduino dengan Bluetooth Via Android - Ira Wati; Sultan Achmed; Titus Y. Agung (Universitas Islam Lamongan, 2022)
The development of science and technology in today's world is very rapid, technological progress is something that cannot be avoided in this life because technological progress will run in accordance with scientific advances. The concept behind the manufacture is the development of an unmanned vehicle control system or commonly called a drone, a vehicle that can be operated without a crew and controlled remotely using Bluetooth installed on a smartphone. Mobile Robot is a robot construction whose characteristic is that it has an actuator in the form of a wheel to move the entire robot body, so that the robot can move positions from one point to another. This Mobile Robot is designed to move using an Android Smartphone controller that has applications that are suitable for robot movement. This robot uses Arduino Uno as a Bluetooth robot control system, the module for the tool made this time uses a Bluetooth module as a data receiver sent via an android smartphone which will then be processed by Arduino and then forwarded to the L298N motor driver which will provide output to move the DC motor according to the command provided wirelessly. The method used is an experimental method, the research carried out will focus on communication between Smartphone devices and the Arduino Uno microcontroller via Bluetooth to control robotic devices. In its implementation it can be applied to reach locations that are difficult or dangerous enough for humans to enter, so that with technology like this it will make it easier for humans to reach these areas without having to enter the location but only by controlling the device remotely.Keywords: Adruino Microcontroller, L298N DC Motor, Bluetooth, Smartphone.